Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.langmuir.6b00543
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Scanning Probe Nanolithography (cSPL): Control of the AFM Parameters in Order to Achieve Sub-100-nm Spatially Resolved Epoxidation of Alkenes Grafted onto a Surface

Abstract: Scanning probe lithography (SPL) appears to be a reliable alternative to the use of masks in traditional lithography techniques as it offers the possibility of directly producing specific chemical functionalities with nanoscale spatial control. We have recently extend the range of applications of catalytic SPL (cSPL) by introducing a homogeneous catalyst immobilized on the apex of a scanning probe. Here we investigate the importance of atomic force microscopy (AFM) physical parameters (applied force, writing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Copyright 2017 Royal Society of Chemistry. (b) Adapted with permission from ref (294). Copyright 2016 American Chemical Society.…”
Section: Alternative Activation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2017 Royal Society of Chemistry. (b) Adapted with permission from ref (294). Copyright 2016 American Chemical Society.…”
Section: Alternative Activation Methodsmentioning
confidence: 99%
“…297304 The technique could be extended to the use of a homogeneous catalyst immobilized onto the tip upon modification with an appropriate ligand (see Figure 26b). 294,305307 The use of a homogeneous catalyst in principle opens the way to a large variety of chemical reactions. It was shown that the catalytic activity of the tip-supported catalyst was barely affected during the reaction process, and large areas could be covalently modified without significant loss of the reactivity.…”
Section: Alternative Activation Methodsmentioning
confidence: 99%
“…The high forces required are consistent with results obtained with related organometallic cSPL methodologies described previously. 33 …”
Section: Resultsmentioning
confidence: 99%
“…A second step of derivatization with piperazine or amine-based moieties was required to reveal the formation of nanostructures. 33 Despite its intrinsic robustness, this catalytic system still suffers from some inherent drawbacks such as: (i) multi-step synthesis of the catalyst supported on the tip, (ii) the necessity of a post-functionalization step to “reveal” the topography of the new nanostructures, and finally, (iii) the impossibility to selectively graft more than one type of molecular objects during the “writing” process (catalysis and post-functionalization).…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach would combine the precision of SPL with the chemical selectivity of catalysis, thereby greatly increasing the chemical scope and complexity that can be achieved by SPL. 1,12 This type of direct synthesis is of particular relevance to the lithography of materials that are otherwise difficult to process by other approaches, such as conducting polymers. For example, polyaniline is a conjugated polymer that exhibits high electrical conductivity and electrochemical stability, and is therefore of interest in the development of organic electronic devices.…”
Section: Introductionmentioning
confidence: 99%